2018
DOI: 10.1186/s12885-018-4932-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of clinicopathologic and surgical factors on relapse and pregnancy in young patients (≤40 years old) with borderline ovarian tumors

Abstract: BackgroundFertility sparing surgery has been extensively performed among patients with borderline ovarian tumors due to their age and favorable prognosis. Nevertheless, the prognosis and obstetric outcomes in these patients remain uncertain. Thus, the current study was carried out to evaluate the oncological safety and fertility benefits of different fertility sparing surgery subtypes and various clinicopathological parameters.MethodsYoung borderline ovarian tumor patients with an age of ≤40 years, who were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 34 publications
2
53
0
Order By: Relevance
“…Factors consistently associated with recurrent BOT in our adjusted analysis included stage and pre‐operative capsule rupture of the primary BOT. Some previous studies have shown that higher FIGO clinical stages were associated with higher BOT recurrence rates . For example, in a study of 339 Italian women, those who had primary BOT at a more advanced stage had a higher recurrence rate (40%) after conservative surgeries, compared with stage I (15%) .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Factors consistently associated with recurrent BOT in our adjusted analysis included stage and pre‐operative capsule rupture of the primary BOT. Some previous studies have shown that higher FIGO clinical stages were associated with higher BOT recurrence rates . For example, in a study of 339 Italian women, those who had primary BOT at a more advanced stage had a higher recurrence rate (40%) after conservative surgeries, compared with stage I (15%) .…”
Section: Discussionmentioning
confidence: 94%
“…Some previous studies have shown that higher FIGO clinical stages were associated with higher BOT recurrence rates. 8,11,[14][15][16][17] For example, in a study of 339 Italian women, those who had primary BOT at a more advanced stage had a higher recurrence rate (40%) after conservative surgeries, compared with stage I (15%). 18 Also, the associations between tumor's characteristics (including rupture and stage) have been observed commonly in other studies 16 ; thus, our results are consistent with these previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the balance between oncological and reproductive outcomes should be assessed adequately; approximately 12%-36% of the patients with BOT who undergo FSS experience recurrence [20], and the most common site of recurrence is the residual ovary [20][21][22][23]. Previous studies have shown that the recurrence rate of BOT in patients who underwent FSS was markedly higher than that in patients who underwent radical surgeries (21.4% vs. 6.3%, P < 0.05) [9,24]. Furthermore, a large proportion of patients who underwent FSS experienced invasive recurrence [13].…”
Section: Discussionmentioning
confidence: 99%
“…Micropapillary lesions were defined as serous borderline tumours containing complex micropapillary structures [9]. Microinvasion was defined as stromal invasion restricted to an area of no more than 10 mm 2 [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation